Head and neck dermatofibrosarcoma protuberans: Case series of extensive resections and reconstructions with literature review [version 1; peer review: 2 approved] - Sawssen Dhembri; Souhail Jbali; Mohamed Dhaha; Rim Braham; Amira Gallas; Yasmine Fertani; Alia Methnani; Ameni Amri; Skander Kedous (F1000Research)
Dermatofibrosarcoma protuberans is a rare, locally aggressive soft-tissue sarcoma. Head and neck involvement accounts for only 10–15% of cases. Achieving clear margins in this region is challenging owing to anatomical constraints. Such cases often require extensive resection and complex reconstructions. This study presents a case series of extensive dermatofibrosarcoma resections in the head and neck, focusing on the surgical margins, reconstruction strategies, recurrence rates, and adjuvant therapy. We report four cases of head and neck dermatofibrosarcoma involving the cheek and scalp. Surgery included wide local excision with margins of 3–5 cm, which was confirmed intraoperatively by frozen section analysis. Reconstruction involved free flaps, local flaps, and healing with secondary intention. The choice depends on the defect size and location. Adjuvant radiotherapy was administered to selected cases. All patients achieved negative margins. One patient developed flap necrosis that required revision surgery. No local recurrence was observed during the follow-up (1–7 years). Head and neck dermatofibrosarcoma justifies aggressive surgical resection to achieve clear margins, which is the key to reducing the risk of recurrence. Free flaps and local reconstruction techniques ensure good functional and aesthetic outcomes. Adjuvant radiotherapy is indicated in patients with close margins or deep invasion. Long-term follow-up is essential owing to its high recurrence potential.